Evaluating a physicians' perspective on the use of probiotics and vitamins against coronavirus disease - Goktas, Olgun; Ersoy, Canan (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the perspective of family physicians on probiotics and vitamins against coronavirus disease-2019. Methods: The cross-sectional study was conducted from June 1 to 30, 2021, after approval from the ethics review committee of Bursa Uludag University, Bursa, Turkey, and comprised family physicians of either gender working at family health centres in the country. Data was collected using an online questionnaire to measure the sociodemographic characteristics, habits, health status related to coronavirus disease-2019, and their knowledge, awareness and behaviour towards the use of probiotics and vitamins during the pandemic. Data was analysed using SPSS 25. Results: Of the 218 family physicians, 130(59.6%) were male and 88(40.4%) were female. The overall mean age was 46.82±5.85 years, mean professional experience was 22.32±8.75 years, and mean experience in family medicine was 10.14±3.51 years. The knowledge and awareness level about coronavirus disease-2019 was high 4.18±0.58, exposure to the disease 3.36±0.83 and their inclination towards the use of vitamins and probiotics 1.68±0.75 was low. Among the participants, 90(41.3%) used probiotic products and 120(55%) used drugs, such as vitamins and minerals. Vitamin C 99(45.4%) was the most commonly used supplement. Conclusion: Physicians' knowledge and awareness and a realistic scientific approach are important when recommending supplements, such as probiotics, vitamins and minerals, to individuals during the pandemic. Key Words: COVID-19, SARS-CoV-2, Probiotics, Vitamins, Survey.